1998
DOI: 10.1183/09031936.98.12040895
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory flow limitation in compressed air divers and oxygen divers

Abstract: Divers are exposed to dense gases under hyperbaric and hyperoxic conditions and, therefore, may be at risk of developing respiratory disease. Long-term effects on respiratory function have been found in commercial divers who perform deep dives. This study was conducted to detect possible lung function changes in scuba divers who dive in shallow water using compressed air or oxygen as a breathing gas. A cross-sectional sample of 180 healthy male divers (152 air divers and 28 oxygen divers) and 34 healthy male c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
2
20
2
Order By: Relevance
“…These findings were taken as evidence to suggest development of small airways disease in divers. Subsequent cross-sectional studies in German Navy scuba divers [42] confirmed a pattern of reduced expiratory flow rates at low lung volumes when compared to non-diving controls, and mid-expiratory flows at 25% and 50% of vital capacity were inversely related to years of diving. However, different group characteristics and selection effects may have confounded the results [43].…”
Section: Long-term Effects Of Diving On Lung Functionmentioning
confidence: 86%
“…These findings were taken as evidence to suggest development of small airways disease in divers. Subsequent cross-sectional studies in German Navy scuba divers [42] confirmed a pattern of reduced expiratory flow rates at low lung volumes when compared to non-diving controls, and mid-expiratory flows at 25% and 50% of vital capacity were inversely related to years of diving. However, different group characteristics and selection effects may have confounded the results [43].…”
Section: Long-term Effects Of Diving On Lung Functionmentioning
confidence: 86%
“…The question whether a single scuba-dive elicits adverse eects on pulmonary function is of concern, since there is consensus that compressed-air diving is associated with long-term respiratory changes. A respiratory pattern indicating dysfunction of the small airways has been the unanimous ®nding of cross-sectional studies in compressed-air divers (Bermon et al 1994;Tetzla et al 1998). In longitudinal surveys a pronounced decrease in the reduction in small airways¯ows and a decrease in gas transfer function have been reported as well (Bermon et al 1994(Bermon et al , 1997.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, hyperoxia and venous gas microembolism may be less important in contributing to eects of compressed-air dives on the lungs of healthy subjects, when these dives are made within the recommended guidelines. Ambient cold may be an important factor since the adverse long-term eects have been reported only in divers who dive predominantly in cold waters (Bermon et al 1994;Tetzla et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement in older participants with a greater amount of diving experience can be primarily connected with the work of the sympathetic nervous system causing the enlargement of the airways lumen, or blocking the action of the parasympathetic system [9,10]. The authors anathematised a possible greater "tolerance" of the trachea and larger bronchi walls to elevate oxygen partial pressures in longer dives because, when assuming the reaction of the bronchial walls to hyperbaric oxygen in the shape of the mucous membrane oedema and the contraction [9,14] after diving, we would not observe the improvement of the parameters researched by means of PEV but their deterioration.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%